Antioxidant Effect of Edaravone on the Development of Preimplantation Porcine Embryos against Hydrogen Peroxide-Induced Oxidative Stress - Geon-Yeop Do; Jin-Woo Kim; Sung-Kyu Chae; Jae-Hyun Ahn; Hyo-Jin Park; Jae-Young Park; Seul-Gi Yang; Deog-Bon Koo (The Korean Society of Animal Reproduction and Biotechnology, 2015)
Edaravone (Eda) is a potent scavenger of inhibiting free radicals including hydroxyl radicals (H2O2). Reactive oxygen species (ROS) such as H2O2 can alter most kinds of cellular molecules such as lipids, proteins and nucleic acids, cellular apoptosis. In addition, oxidative stress from over-production of ROS is involved in the defective embryo development of porcine. Previous study reported that Eda has protective effects against oxidative stress-like cellular damage. However, the effect of Eda on the preimplantation porcine embryos development under oxidative stress is unclear. Therefore, in this study, the effects of Eda on blastocyst development, expression levels of ROS, and apoptotic index were first investigated in preimplantation porcine embryos. After in vitro fertilization, porcine embryos were cultured for 6 days in PZM medium with Eda (10 μM), H2O2 (200 μM), and Eda+H2O2 treated group, respectively. Rate of blastocyst development was significantly increased (P<0.05) in the Eda treated group compared with only H2O2 treated group. And, we measured intracellular levels of ROS by DCF-DA staining methods and investigated numbers of apoptotic nuclei by TUNEL assay analysis is in porcine blastocyst, respectively. Both intracellular ROS levels and the numbers of apoptotic nucleic were significantly decreased (P<0.05) in porcine blastocysts cultured with Eda (10 μM). More over, the total cell number of blastocysts were significantly increased (p<0.05) in the Eda-treated group compared with untreated group and the only H2O2 treated group. Based on the results, Eda was related to regulate as antioxidant-like function according to the reducing ROS levels during preimplantation periods. Also, Eda is beneficial for developmental competence and preimplantation quality of porcine embryos. Therefore, we concluded that Eda has protective effect to ROS derived apoptotic stress in preimplantation porcine embryos.